2005
DOI: 10.1097/00001888-200503000-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical, Practical, Predictive Model of Faculty and Department Research Productivity

Abstract: The characteristics and groupings (individual, institutional, and leadership) in the Bland et al. (2002) model predict faculty research productivity. Research productivity is influenced by the interaction of the three broad groupings, and it is the dynamic interplay of individual and institutional characteristics, supplemented with effective leadership, that determines the productivity of individuals and departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
275
5
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(316 citation statements)
references
References 14 publications
25
275
5
11
Order By: Relevance
“…17,18 Having tenure, having completed a doctorate, and having completed a fellowship program are predictive of scientific publishing. [19][20][21][22] An adequate period of time dedicated to publishing activities is an important predictive factor in scientific publishing. 17,20,22 Our study found that a higher number of respondents from France had at least 1 publication in their name, whatever the type of publication evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Having tenure, having completed a doctorate, and having completed a fellowship program are predictive of scientific publishing. [19][20][21][22] An adequate period of time dedicated to publishing activities is an important predictive factor in scientific publishing. 17,20,22 Our study found that a higher number of respondents from France had at least 1 publication in their name, whatever the type of publication evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] An adequate period of time dedicated to publishing activities is an important predictive factor in scientific publishing. 17,20,22 Our study found that a higher number of respondents from France had at least 1 publication in their name, whatever the type of publication evaluated. Nevertheless, there were several differences between respondents from France and Quebec.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23] Critical mass of research capacity within an institution is thought to be an important determinant of research success. 13 To measure critical mass, we measured the number of researchers who submitted applications from the same institution as the principal investigator for the same competition.…”
Section: Potential Predictors Of Cihr Funding Successmentioning
confidence: 99%
“…Bland et al (2005) investigated characteristics in a large medical school in the US. They found that certain individual, institutional and leadership characteristics are related to research productivity.…”
mentioning
confidence: 99%